Cross-sectional analysis of fouled SWRO membranes by STEM-EDS - Aubry, C.; Khan, M.; Behzad, A.; Anjum, D.; Gutierrez, L.; Croue, Jean-Philippe (2014)
The intact cross-section of two fouled reverse osmosis membranes was characterized using a scanning transmission electron microscope (STEM) equipped with an electron energy dispersive spectroscope (EDS). Focused ion beam (FIB) was used to prepare a thin lamella of each membrane. These lamellas were then attached to a TEM grid for further STEM/EDS analysis. The foulant in sample A was mainly inorganic in nature and predominantly composed of alumino-silicate particles. These particles were surrounded by carbon at high concentrations, indicating the presence of organic materials. Iron was diffusely present in the cake layer and this could have enhanced the fouling process. The cake layer of membrane B was mainly consisted of organic matter (C, O, and N representing 95% of the total elemental composition) and organized in thin parallel layers. Small concentrations of Si, F, Na, Mg, and Cl were detected inside the active layer and support layer of the membrane. Due to the high sensitivity of the cake layer of membrane A to the electron beam, STEM/EDS line analyses might have been performed on large areas. On the other hand, the cake layer of sample B was resistant to the electron beam and the resolution of STEM/EDS was gradually improved until obtaining a resolution of 25. nm.